INFORMATION SYSTEM FOR DISASTER MANAGEMENT DATA PROCESSING AT THE REGIONAL DISASTER MANAGEMENT AGENCY (BPBD) OF NORTH ACEH REGENCY - Hizamrul Jaen; Irham Fatriyandas Rufdo; Muhammad Irsyad Thoyib (Bulletin of Engineering Science, Technology and Industry, 2023)
This research aims to address the pressing need for an efficient and comprehensive information system application for disaster management. Natural disasters can have devastating impacts on communities, and effective disaster management is crucial to minimize losses and ensure a swift and well-coordinated response. To meet this objective, the study develops a website-based application that manages critical disaster-related data, such as information on disaster victims, aid distribution, handling processes, and visual documentation (photos and videos) of the disaster. The design of the application incorporates three essential methodologies: Data Flow Diagrams (DFD), Entity-Relationship Diagrams (ERD), and Context Diagram. These methodologies ensure a clear and systematic representation of data flow, database structures, and system boundaries. By utilizing these tools, the researchers ensure the application's efficiency, effectiveness, and user-friendliness in managing disaster-related information. The research employs a mixed-method approach, combining quantitative and qualitative data collection techniques. Surveys, interviews, and observations are conducted to assess the application's usability, effectiveness, and impact on disaster management. Quantitative data is analyzed using statistical tools, while qualitative data is thematically analyzed to gain deeper insights into user experiences and perceptions.